Evidence, objectivity and welfare reform: a qualitative study of disability benefit assessments. (1st May 2021) - Porter, Tom; Pearson, Charlotte; Watson, Nick
Abstract : Background: Anti-welfare narratives depict welfare systems as overly-permissive, open to fraud, and fundamentally unfair. Countering these supposed ills have been political appeals to evidence and reforms made to disability benefit assessments under the banner of objectivity. But objectivity is a complex construct, which entails philosophical and political choices that tend to oppress, exclude and symbolically disqualify alternative perspectives.Aims and objectives: To examine reforms made to UK disability benefits assessments in the name of objectivity.Methods: Thematic analysis of 50 in-depth qualitative interviews with UK disability benefit claimants.Findings: Reforms made in pursuit of procedural objectivity reproduce existing social order, meaning claimants without personal, social and economic resources are less likely to succeed. Data reveal an increasingly detached and impersonal assessment process, set against a broader welfare landscape in which advocacy and support have been retrenched. In this context, attaining a valid and reliable assessment was, for many, contingent upon personal, social and economic resources.Discussion and conclusions: Political appeals to evidence helped establish an impetus and a legitimising logic for welfare reform. Procedural objectivity offers superficially plausible, but ultimately specious, remedies to longstanding anti-welfare tropes. Despite connotations of methodological neutrality, procedural objectivity is not a politically neutral epistemological standpoint. To know disability in a genuinely valid and reliable way, knowledge-making practices must respect dignity and proactively counter exclusory social order. These latter principles promise outcomes that are more trustworthy by virtue of their being more just.